N-Heterocyclic carbene catalyzed oxidative coupling of alkenes/alpha-bromoacetophenones with aldehydes: a facile entry to alpha,beta-epoxy ketones - Reddi, Rambabu N.; Prasad, Pragati K.; Sudalai, Arumugam (Angewandte Chemie-International Edition, 2015)
{A novel, N-heterocyclic carbene (NHC) catalyzed direct oxidative coupling of styrenes with aldehydes has been described for the synthesis of alpha,beta-epoxy ketones in good yields. This unprecedented regioselective oxidative coupling employs NBS/DBU/DMSO (DBU = 1,8-diazabicyclo [5.4. 0] undec-7-ene
Keywords: aldehydes; epoxidation; N-heterocyclic carbenes; Oxidation; synthetic methods